Incarcereted Epigastric Hernia with Liver Content: a Case Report - Ozkan, Cenk; Yilmaz, Serhan; Sibic, Osman (Lietuvos chirurgija, 2024)
The epigastric hernia sac usually contains preperitoneal fat tissue, omentum, and intestines, but the presence of liver tissue is extremely rare. Epigastric hernia is a type of hernia in the midline of the abdominal wall between the umbilicus and the xiphoid process. It may be asymptomatic in some patients and cause complaints such as pain and nausea in most patients, but serious complications such as incarceration and strangulation are rare. In the present case, a 74-year-old woman was examined and found to have an irreduced omentum, transverse colon and liver tissue inside the hernia sac. She underwent an open procedure with onlay mesh-assisted hernia repair. Rare but serious complications, such as liver tissue incarceration, should be considered in epigastric hernia patients.